Improving the Vietnamese Accreditation in Light of the SACSCOC’s Institutional Effectiveness Standards - Nhung, Pham Thi Tuyet (VNU Journal of Science: Education Research; Vol 34 No 3DO - 10.25073/2588-1159/vnuer.4164, 2018)
The purpose of this study was to explore Vietnamese educators’ perspectives regarding the feasibility of implementing a U.S. Regional Accreditation standard (“Institutional Effectiveness”) in the current Vietnamese higher education accreditation standards. An Institutional Effectiveness (IE) Process (Strategic Planning-Planning and Assessment- Operational Planning) and Assessment Cycle (Program Learning Outcomes-Curriculum Map-Assessment Methods-Data Collection-Actions for Improvement) served as the conceptual framework for this study. The qualitative research design involved interviews with seven Vietnamese educators who work in centers for accreditation and offices of quality assurance in Vietnamese universities. Findings indicated that all participants supported the implementation of an IE standard and Assessment Cycle in Vietnamese higher education accreditation. Findings also stated that currently the IE Process and Assessment Cycle are not fully implemented in Vietnam higher education accreditation. The Vietnamese higher education institutions (HEIs) did not have a supportive culture of strategic planning due to centralized management by the Ministry of Education and Training (MOET). Moreover, most universities were only familiar with the first two steps in the Assessment Cycle. Based on the research findings, recommendations for the implementation of IE process and Assessment Cycle are made for MOET, Centers for Accreditation and Vietnamese HEIs.